How Regulations Impact the Labor Market: A Review of the Literatures on Product and Labor Market Regulations - David Alzate; Eliana Carranza; Joana Duran-Franch; Truman Packard; Celina Proffen (Institute of Labor Economics (IZA), 2024)
This paper provides an extensive review of the literatures on product and labor market regulations and their effects on labor market outcomes. It uncovers the interdependence of these two types of regulations, an area that has received limited attention in research. The paper highlights why understanding the intricate relationship between product and labor market regulations is crucial for effective policy making and advancement of labor market conditions. The findings strongly discourage adopting uniform policies and advocate for tailored approaches to labor market promotion.
Keywords: J20; J30; J8; K2; L5; 330; labor market regulation; product market policy; employment; wage; productivity; worker protection; firm competition; public policy